Ruptura distální šlachy musculus biceps brachii – korelace sonografických a operačních nálezů, výsledky operační terapie - Grinac, Michal; Brtková, Jindra; Kučera, Tomáš; Šponer, Pavel (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2018)
PURPOSE OF THE STUDY When treating tears of the distal biceps brachii muscle tendon, we repeatedly noticed a difference between the preoperative ultrasound findings and the operative findings. The aim of the study was to retrospectively correlate these findings in order to determine the sensitivity of the ultrasound examination in everyday orthopaedic practice. Moreover, we compared the results and complications of surgical treatment through two operative techniques used at our department. MATERIAL AND METHODS In the 2004-2016 period 20 patients underwent a surgery at our department for total tear of the distal tendon of the biceps brachii muscle. In 18 patients an ultrasound examination was performed preoperatively. In 3 patients it was repeated. Therefore, there were a total of 21 ultrasound observations made in this group of patients. Excluded were the cases of chronic tendinoses or inveterated tears. The group was divided into two sub-groups. The first sub-group was composed of patients in whom the preoperative ultrasound examination was performed by a radiologist-specialist in the musculoskeletal system, the second sub-group was composed of patients examined by a non-specialist. The ultrasound findings were compared with the operative findings. With the use of a formula for the calculation of sensitivity of the test, the sensitivity of the ultrasound examination was determined for proper recognition of a complete tear of the tendon concerned. Also, we compared the results and complications of the two operative methods applied: the technique using bone anchor vs. the Boyd-Anderson technique of transosseous reinsertion. RESULTS The sensitivity of the ultrasound examination was 91% in examinations performed by a radiologist-specialist and 40% in examinations performed by no-specialists. Both the surgical techniques brought very good results in our group of patients. The reported complications included 2 cases of temporary radial nerve palsy, 1 case of formation of heterotopic ossifications. DISCUSSION The sensitivity of ultrasound is adequate according to the literature. In our group of patients, the same applied only to examinations performed by a radiologist-specialist in the musculoskeletal system. This is because the ultrasound examination of the distal biceps tendon is a highly specialised examination. When performed by a non-specialist, the result of examination obtained in our observations is rather misleading, thus could lead to an improper method of treatment. Partial tears of this tendon are very rare according to the literature. Indirect signs of the partial tear presence at this location detected by ultrasound resulted in most cases in an incorrect diagnosis, therefore the description of a partial tear visualised by the ultrasound should be reserved exclusively for cases when intact fibrils are clearly detected during the examination. For unclear cases, the MRI scan is indicated. The results of both the surgical techniques of reinsertion applied were very good. The method using the bone anchors is technically easier to perform. Nonetheless, it has its specifics. CONCLUSIONS To diagnose correctly the tear of the distal biceps muscle tendon it is essential to perform a thorough clinical examination and to obtain the medical history of the patient, especially the mechanism of injury. Sonography can be beneficial only provided the examination is carried out by a specialist in the musculoskeletal system, with the use of appropriate device and under standard conditions. For surgical treatment of this injury we prefer the technique using a bone anchor, namely particularly since it is technically easier to perform. The functional results are very good. Key words: distal biceps tendon, elbow, tendon tear, ultrasound, suture anchors.
Keywords: Correlation of Data; dospělí; kosterní svaly; Suture Anchors; Tenodesis; Female; Radial Neuropathy; ultrasonografie; Adult; výsledek terapie; ženské pohlaví; Tendons; paže; lidé; neuropatie nervus radialis; Sensitivity and Specificity; Ultrasonography; pooperační komplikace; Treatment Outcome; Muscle, Skeletal; senzitivita a specificita; šlachy; kotvící implantáty; poranění šlachy; Male; Postoperative Complications; tenodéza; mužské pohlaví; Arm; Tendon Injuries; korelace dat; Humans